Violation of Right to Liberty and Security in the Assessment of Claims for Asylum - Hrnčárová, Nataša (Lidé města, 2014)
The European Union’s asylum acquis has been built on the common understanding that some of those third country nationals who seek to enter the territory of the European Union have a well-founded fear of persecution or, due to the real risk of suffering serious harm they cannot return to their country of origin. Their background distinguishes them clearly from other migrants and has made it necessary to provide them with a special protective status. It can be assumed that, within the European Union, there exist different but overlapping legal institutions for those third country nationals seeking international protection in the European Union and are in need of international protection for the abovementioned reasons. The most important ones are the 1951 Geneva Convention relating to the Status of Refugees (the Convention), the Law of the European Union (the Convention’s Protocol of 1967), and the 1950 Convention for the Protection of Human Rights and Fundamental Freedoms (“ECHR”) and its protocols.